USE OF DISTANCE LEARNING TECHNOLOGIES IN PREPARATION OF A FUTURE TEACHER OF MATHEMATICS - T.H. Kramarenko (Academy of Cognitive and Natural Sciences, 2010)
In the article experience of the use of electronic teaching environment оf Moodie is presented in the conditions of the stationary teaching with the purpose of forming of methodical competence of future teachers of mathematics.